Heartburn and effective herbal remedies: A systematic review study in Iranian ethnobotanical documents - Gholam Basati; Pardis Ghanadi; Pegah Shakib; Majid Hamidi; Peyman Amanolahi Baharvand (Shahrekord University of Medical Sciences, 2021)
Every year, millions of people worldwide get sick with gastrointestinal diseases such as heartburn. Certain herbs contribute to the alleviation of heartburn, nausea, and improvement of digestion. Moreover, these herbs do not have as many side effects as synthetic drugs. As a health problem and one of the challenging issues in medical sciences, heartburn is common in children and adults worldwide. Hence, in the present study, we tried to report medicinal plants used in cultures and traditions of different regions of Iran to treat heartburn in children and adults. In this review study, articles of Iranian ethnobotanical sources were searched with the keywords of ethnobotanics, heartburn, children, adult, medicinal plants, and Iran. Journal articles published from 2010 to 2019 in several Iranian and International databases, including ISI Web of Science, PubMed, Scopus, ISC, Magiran, were searched to find relevant articles and information. Anethum graveolens L., Punica granatum L., Mentha pulegium, Thymus kotschyanus Boiss. & Hohen., Achillea millefolium, Ocimum basilicum, Nigella sativa, etc., are the plants used in different parts of Iran to treat heartburn.